1976
DOI: 10.1530/jrf.0.0480209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of administration of progesterone and oestrogen on litter size in pigs

Abstract: Summary. Progesterone and oestrone alone or in combination were administered to sows during early gestation. A dose of 25 mg progesterone and 12\m=.\5 \g=m\g oestrone injected together for 10,5 or 2 consecutive days during the implantation interval caused increased litter size at term.The effect of exogenous steroid hormones on embryonic survival in the pig is unclear. While pro¬ gesterone given alone during gestation has no, or even a detrimental effect on embryo viability (Sammelwitz, Dziuk & Nalbandov, 1956… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Whether or not FSH contributes to influence luteal function remains speculation. If we were to accept previous reports that steroid treatments in pigs [8,9] or GnRH in horses [30,31] benefit pregnancy outcome, other routes of GnRH mediation could also be evident, such as those influencing processes of uterine estrogen synthesis [32], endometrial angiogenesis, utero-ovarian counter-current transfer [33] and P4 dependent immunomodulation [34,35]. Furthermore, direct effects of GnRH on ovarian luteal cells [36] and on uterine tissues mediated by extrapituitary receptors should be recognized [37,38].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Whether or not FSH contributes to influence luteal function remains speculation. If we were to accept previous reports that steroid treatments in pigs [8,9] or GnRH in horses [30,31] benefit pregnancy outcome, other routes of GnRH mediation could also be evident, such as those influencing processes of uterine estrogen synthesis [32], endometrial angiogenesis, utero-ovarian counter-current transfer [33] and P4 dependent immunomodulation [34,35]. Furthermore, direct effects of GnRH on ovarian luteal cells [36] and on uterine tissues mediated by extrapituitary receptors should be recognized [37,38].…”
Section: Discussionmentioning
confidence: 97%
“…Attempts have been undertaken to improve pregnancy rate or reduce pregnancy losses in pigs by steroid or gonadotropin application [5][6][7]. Since steroid treatment may improve litter size [8,9], the question is whether luteal P4 secretion can be enhanced by GnRH-induced LH stimulation. This is because LH is considered to be essential in pigs for support of luteal P4 production and pregnancy outcome as demonstrated by passive immunization with anti-LH serum or blockage of LH secretion and regulation of ovarian function by a GnRH antagonist [10,11].…”
mentioning
confidence: 99%
“…Studies to determine the effects of exogenous progesterone on embryonic survival are not conclusive (Day et aL, 1959;Spies et al, 1959;Schultz et al, 1966;Wildt et al, 1976). Studies of the relationship between plasma progesterone concentrations or progesterone metabolites in the urine and embryo numbers have yielded inconsistent results (Mayer et al, 1961;Tillson and Erb, 1970;Edgerton et al, 1971;Rampacek and Ulberg, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…The results of two field trials undertaken by Wildt, Culver, Morcom & Dukelow (1976) also indicated that treatment of sows with progesterone and oestrone (2000:1) during early pregnancy had a beneficial effect on embryo survival, although the findings were not wholly unequivocal. In the main trial, an increase of approximately 20% in litter size at birth was recorded in the treated animals, but in a second trial no significant difference was observed between the treated and control groups.…”
Section: Introductionmentioning
confidence: 99%